Occurrence of third-generation cephalosporin-resistant Escherichia coli in European hedgehogs (Erinaceus europaeus) from a wildlife rescue centre in Lombardy, Northern Italy - S. Raineri; A. Gazzola; G. Dilio; S. Ventura; A. M. Maisano; F. Guarneri; N. Formenti; G. L. Alborali; C. F. Magistrali; J. Filipe; Maria Cristina Rapi; G. Grilli (Veterinary Research Communications, 2026)
Hedgehogs represent a promising indicator for evaluating environmental health. We investigated the occurrence of third-generation cephalosporin-resistant (3GCR) Escherichia coli in intestinal contents from 49 European hedgehogs ( Erinaceus europaeus ) deceased at a Wildlife Rescue Centre in Lombardy, Northern Italy. Bacteriological analysis was performed to isolate 3GCR- E. coli ; antimicrobial-resistance (AMR) profiles of the isolates were evaluated by broth dilution (MIC). The presence of bla CTX−M, bla TEM , bla SHV , bla CMY−2 genes was assessed by PCR assay. 3GCR- E. coli were detected in 51% of the examined hedgehogs ( n = 25/49). The majority of the isolates were multidrug resistant (MDR); resistance was recorded against the β-lactams cefotaxime, cefazolin, and ampicillin in 100% ( n = 25/25) of isolates while amoxicillin/clavulanic acid in 52% ( n = 13/25). Resistance against enrofloxacin and flumequine was found in 92% ( n = 23/25) of isolates and tetracycline in 64% ( n = 16/25). All the isolates were susceptible to colistin and florfenicol, and most of them were susceptible to kanamycin (96%, n = 24/25). The most frequently detected resistance gene was bla TEM (52%, n = 13/25), followed by bla SHV (36%, n = 9/25) and bla CTX−M (28%, n = 7/25). Seven isolates carried two ESBL genes, five being bla TEM / bla SHV , and two bla TEM / bla CTX−M . No isolates harbored bla CMY−2 gene. Our study provides the first data on the occurrance of 3GCR- E. coli in European hedgehogs admitted to a wildlife rescue centre in Northern Italy. However, since the sampled animals were not collected through a field-based survey, the findings should not be considered representative of the wider free-ranging population. Nonetheless, resistance profiles and genomic characterization of these isolates provide useful information on AMR circulation in human-impacted environments.

Soil Microbial Diversity and Network Organization Respond to Land Use and Agricultural Inputs Worldwide - Zaki Saati‐Santamaría; Sergio Pérez‐Gorjón; Daniel Abel‐Schaad; Alberto Acedo‐Bécares; Francisca Alba‐Sánchez; Amanda Lucia Alves; Weronika Babinska‐Wensierska; Jorge Ariel Marfetán; Carolina Barroetaveña; Kara Barry; Francisco Beitia; Katerina Biniari; et al. (Global Change Biology, 2026)
Soil microbiomes are critical for ecosystem functioning, yet the global influences of climate and agricultural practices on their diversity and structure remain incompletely characterized. Here we analyzed 1921 soil samples from 33 countries worldwide across diverse biomes to assess how climate gradients and agricultural inputs, including pesticides and fertilizers, shape prokaryotic and fungal communities. We found that microbial diversity peaks at intermediate temperatures and differs markedly between natural and agricultural soils, with agriculture increasing microbial diversity while altering community composition and ecological guilds. Pesticide use selectively reduced bacterial diversity and shifted fungal guilds, decreasing ectomycorrhizal fungi while increasing saprotrophs, whereas fertilization reduced microbial network cohesion, with organic and inorganic fertilizers eliciting distinct community responses. These findings reveal that climatic factors and agricultural management jointly influence soil microbial diversity, community structure, and network connectivity, with implications for soil health and ecosystem resilience in managed landscapes. Overall, our results demonstrate that agricultural practices, including the use of pesticides and both organic and inorganic fertilizers, act as strong ecological filters that reshape soil microbiomes worldwide—enhancing apparent diversity but driving a functional shift toward less mutualistic, more fragmented, and potentially less resilient communities.

Chemically untreated recycled silicon from PV panels for the sustainable production of Li-ion battery anodes - M. L. Protopapa; E. Burresi; L. Capodieci; D. Carbone; A. Fiore; S. Grilli; B. Palazzo; M. Palmisano; E. Pesce; E. Salernitano; M. Schioppa; N. Taurisano; et al. (Clean Technologies and Environmental Policy, 2026)

Landscape configurations with greater seminatural habitat and edge density enhance soybean yield across multiple spatial scales - Leonardo D. Amarilla; Gabriel Grilli; Daihana S. Argibay; Agustín Vargas Clérico; Pablo Y. Huais; Mariana P. Mazzei; Nicolás Szawarski; Carolina Torres; Matías Maggi; José L. Vesprini; Leonardo Galetto (Field Crops Research, 2025)

Tsunami hazard assessment along the US East Coast from extreme sources in the North Atlantic Ocean: a limited probabilistic analysis - Stephan T. Grilli; Lauren Schambach; Maryam Mohammadpour; Annette R. Grilli; James T. Kirby; Edward S. Fratto; Fengyan Shi (Natural Hazards, 2025)
Coastal hazard is assessed along the US East Coast (USEC) through model simulation of 14 probable maximum tsunamis (PMTs) from sources located in the North Atlantic Ocean basin, in terms of: (i) standard inundation maps and other hazard products, and (ii) a limited probabilistic tsunami hazard analysis (PTHA) based on these. Tsunami sources are based on historical records or are hypothetical, including extreme seismic events in the Puerto Rico Trench (PRT)/Caribbean Arc area and in the Açores Convergence Zone (ACZ), near-field submarine mass failures (SMF) on or near the continental shelf break, and large scale volcanic flank collapses of the Cumbre Vieja Volcano (CVV), on La Palma in the Canary Archipelago. Various state-of-the-art models are used to simulate tsunami generation from these sources and propagation to the USEC, in a series of nested grids, by one-way coupling. Based on these results, hazard metrics are computed for each PMT and their envelope as: (i) a synoptic representation along the entire USEC (with results interpolated on the 5 m isobath in coarse 450 m grids), and (ii) high-resolution (10–30 m) inundation maps, for about 30% of the USEC to date, prioritizing the most exposed areas. While existing maps can be accessed in a repository, in this paper, we focus on assessing the synoptic tsunami hazard using 4 hazard metrics (surface elevation, flow velocity, momentum force and arrival time) and their combination into a Tsunami Intensity Index ( TII ) introduced in earlier work. A comparison of metrics for each PMT shows similar alongshore patterns of higher/lower impact, due to wave focusing and defocusing effects induced by the shelf bathymetry; on this basis, 14 focusing areas are identified from Maine to southern Florida, where tsunami hazard for any PMT is always relatively larger. The limited PTHA is then performed based on the PMT metrics, using estimated return period ranges for each source (in the $$T_r\in [500; 50,000]$$ T r ∈ [ 500 ; 50 , 000 ] year interval), from the literature and/or educated guesses. This analysis yields return periods along the USEC for 5 classes of metrics and the TII . The PTHA results are then interpolated to provide the same metrics along the USEC for $$T_r = 500$$ T r = 500 and 2,500 years, which are standard in geohazard assessment. PTHA results show, depending on low-high estimates of PMT return periods that: (i) up to $$T_r = 137-261$$ T r = 137 - 261 years, there is no probable tsunami hazard; (ii) for $$T_r =500$$ T r = 500 years, tsunami hazard would be expected to be low-medium and only larger near some focusing sites, with flooding metrics at par with a severe coastal storm; and (iii) for $$T_r =2,500$$ T r = 2 , 500 years, which is commensurate with the longest return periods considered on the US west Coast for large Cascadia events, the USEC would face high tsunami hazard, with widespread destruction near the focusing areas and severe impact elsewhere. As uncertainties are large on the estimated return period ranges used and, hence, on the results of this limited PTHA, while raising awareness for the potential tsunami hazard facing the USEC, this work stresses the need for conducting a more in-depth and comprehensive PTHA, including using a larger selection of tsunami sources and further supporting and refining the range of return periods selected for each of those. Such work has been initiated and will be the object of future papers.

Microbial, physical and chemical indicators together reveal soil health changes related to land cover types in the southern European sites under desertification risk - F.A. Rutigliano; R. Marzaioli; E. Grilli; E. Coppola; S. Castaldi (Pedobiologia, 2023)

At‐vessel mortality of skates (Rajidae) taken in coastal fisheries and evidence of longer‐term survival - J. R. Ellis; G. J. Burt; G. Grilli; S. R. McCully Phillips; T. L. Catchpole; D. L. Maxwell (Journal of Fish Biology, 2018)
Data on the vigour and at‐vessel mortality (AVM) of 6798 skates (comprising Raja clavata n = 6295; R. brachyura n = 208; R. undulata n = 185, R. montagui n = 98 and R. microocellata n = 12) captured by commercial fishing vessels in the inshore waters of the southern North Sea and English Channel were recorded. AVM in longline fisheries averaged 0·44% across five vessels (0–1·47%), although skates were usually unhooked manually and did not usually pass through a bait‐stripper. AVM in otter trawls averaged 0·76% (0–2·35%), from four vessels fishing with tow durations of R. clavata caught by longline and tangle nets in better condition than those captured by otter trawl or drift trammel net. Similarly, R. undulata caught by tangle net were in better condition than those caught by otter trawl. The vigour of R. undulata was also found to be higher than other skate species for both trawl and tangle net. In total, 5283 skates were tagged with Petersen discs and released, with recapture rates for the various combinations of vessel and gear ranging up to 24·8% for R. clavata . Whilst confirming a degree of post‐release survival, quantitative estimates of post‐release mortality for skates remain unknown.

Mycorrhizal fungi affect plant growth: experimental evidence comparing native and invasive hosts in the context of forest fragmentation - G. Grilli; C. Urcelay; M. S. Longo; L. Galetto (Plant Ecology, 2014)

Isolation of Pseudobutyrivibrio ruminis and Pseudobutyrivibrio xylanivorans from rumen of Creole goats fed native forage diet - D. J. Grilli; M. E. Cerón; S. Paez; V. Egea; L. Schnittger; S. Cravero; M. Sosa Escudero; L. Allegretti; G. N. Arenas (Folia Microbiologica, 2013)

Numerical Simulation of the 2011 Tohoku Tsunami Based on a New Transient FEM Co-seismic Source: Comparison to Far- and Near-Field Observations - Stephan T. Grilli; Jeffrey C. Harris; Tayebeh S. Tajalli Bakhsh; Timothy L. Masterlark; Christodoulos Kyriakopoulos; James T. Kirby; Fengyan Shi (Pure and Applied Geophysics, 2013)

Mechanisms related to the cardioprotective effects of protein kinase C epsilon (PKC ɛ) peptide activator or inhibitor in rat ischemia/reperfusion injury - Jane Chun-wen Teng; Helen Kay; Qian Chen; Jovan S. Adams; Christopher Grilli; Giuseppe Guglielmello; Christopher Zambrano; Samuel Krass; Adrian Bell; Lindon H. Young (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Intracellular localization of calcium, phosphorus and nitrogen in common bean seeds ( Phaseolus vulgaris L. cv. Borlotto) by SEM, ESI and EELS techniques - A. Canini; D. Leonardi; M. Grilli Caiola; S. Ruggeri; E. Carnovale (Plant Biosystems, 2001)

Genome analysis of influenza B virus strains isolated during epidemics in boarding schools - A. M. Tikhonova-Heider; A. I. Klimov; A. J. Smith; B. Grilli; J. S. Oxford; Y. Z. Ghendon (Archives of Virology, 1986)